2014
DOI: 10.1371/journal.pone.0094811
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Falls as Novelties in Acceleration Patterns Acquired with Smartphones

Abstract: Despite being a major public health problem, falls in the elderly cannot be detected efficiently yet. Many studies have used acceleration as the main input to discriminate between falls and activities of daily living (ADL). In recent years, there has been an increasing interest in using smartphones for fall detection. The most promising results have been obtained by supervised Machine Learning algorithms. However, a drawback of these approaches is that they rely on falls simulated by young or mature people, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
113
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(122 citation statements)
references
References 27 publications
5
113
3
1
Order By: Relevance
“…Finally, studies on this topic confirm the activities we selected are common in real-life [16,[29][30][31].…”
Section: Of 14mentioning
confidence: 53%
See 1 more Smart Citation
“…Finally, studies on this topic confirm the activities we selected are common in real-life [16,[29][30][31].…”
Section: Of 14mentioning
confidence: 53%
“…It allows measurements of acceleration in three perpendicular axes, and allows acceleration ranges from ±2g to ±16g and sampling rates from 1KHz to 32Hz. For the experiments presented in this paper, the sampling rate was about 50 Hz, which is commonly used in literature for activity recognition from data acquired through smartphones [15][16][17]. The accelerometer signal is for each time instant made of a triplet of numbers (x, y, z) that represents the accelerations along each of the 3 Cartesian axes.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…This could lead to a dramatic decrease in performance when using the detectors in a real-world context, resulting in the rejection of the technology by its potential users. The personalization and adaptation of the system are key aspect to overcome this problem [20].…”
Section: -Discussionmentioning
confidence: 99%
“…In this regard, several authors have identified the need for having public datasets [19,20]. Some efforts have been performed in this direction since several datasets were made publicly available in the recent years: DLR [21] published in 2011, MobiFall [22] available in 2013 and tFall [20] uploaded in 2014 (the study of Fudickar et al [23] cites another public dataset but it seems that it cannot be downloaded currently).…”
mentioning
confidence: 99%
See 1 more Smart Citation